2015
DOI: 10.1002/art.39116
|View full text |Cite
|
Sign up to set email alerts
|

Role of EFNB1 and EFNB2 in Mouse Collagen‐Induced Arthritis and Human Rheumatoid Arthritis

Abstract: Objective EFNB1 and EFNB2 are ligands for Eph receptor tyrosine kinases. This study was undertaken to investigate how the expression of Efnb1 and Efnb2 on murine T cells influences the pathogenesis of collagen‐induced arthritis (CIA) and to assess correlations between the T cell expression of these 2 molecules and measures of disease activity in patients with rheumatoid arthritis (RA). Methods CIA was studied in mice with T cell–specific deletion (double gene knockout [dKO]) of both Efnb1 and Efnb2. Expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…Other mice deficient in several Eph have no phenotype ( 59 , 60 ), and in other experimental models, altered mature mTEC do not course with autoimmune reactivity ( 63 ). Other authors however, have concluded that ephrin-B1 and ephrin-B2, the main ligands of EphB2 and EphB3, are necessary for the proper development of Th1 and Th2 cell subsets ( 64 66 ). Some authors have explained these results indicating that defects in some thymic areas do not affect the functional maturation of thymocytes ( 67 , 68 ).…”
Section: Discussionmentioning
confidence: 98%
“…Other mice deficient in several Eph have no phenotype ( 59 , 60 ), and in other experimental models, altered mature mTEC do not course with autoimmune reactivity ( 63 ). Other authors however, have concluded that ephrin-B1 and ephrin-B2, the main ligands of EphB2 and EphB3, are necessary for the proper development of Th1 and Th2 cell subsets ( 64 66 ). Some authors have explained these results indicating that defects in some thymic areas do not affect the functional maturation of thymocytes ( 67 , 68 ).…”
Section: Discussionmentioning
confidence: 98%
“…In different settings, both up‐ or down‐regulation of che‐ morepellent factors, such as Netrin‐1, during organ injury may exacerbate inflammation (3, 5). It has been also observed that ephrins (EFNB1 and EFNB2) in T cells are essential for pathogenic antibody production and for T‐cell migration to inflamed paws in mice with collagen‐induced arthritis; T cells from patients with RA expressed higher EFNB1 mRNA levels, which correlate with RA symptoms and biomarkers (38).…”
Section: Discussionmentioning
confidence: 99%
“…However, other authors have found poor in vitro responses of EphB6 −/− T cells after anti-CD3 plus anti-CD28 stimulation together as well as in vivo decreased hypersensitivity and autoimmune responses ( 35 ). On the other hand, the deletion of either ephrin-B1 or ephrin-B2 in thymocytes does not course with thymus phenotypes ( 36 , 37 ) but the lack of two molecules results in alterations in thymocytes and thymic structure ( 38 ), and low sensitivity to different autoimmune models, including experimental autoimmune encephalomyelitis ( 39 ) and collagen-induced arthritis ( 40 ). We also observed decreased values of positive selected TCRαβ hi CD69 + thymocytes in ephrin-B1 and/or ephrin-B2 deleted in TECs, particularly when using outbred mouse strains.…”
Section: T-cell Development In An Altered Thymic Epitheliummentioning
confidence: 99%